Ongehoorde taal : boeken voor dove kinderen - Le Grand, Maaike (Den Haag : Nederlands Bibliotheek en Lektuur Centrum, 1985)
Lit.opg.
Bibliography: p. 54-75.
Keywords: Children -- Books and reading -- Netherlands; Children's literature, Dutch -- Bibliography